Investigating fish behavioural responses to LED lights in trawls and potential applications for bycatch reduction in the Nephrops-directed fishery. (18th April 2018) - Melli, Valentina; Krag, Ludvig A; Herrmann, Bent; Karlsen, Junita D; ,
Abstract: Light-emitting diodes (LEDs) have been tested in trawl fisheries to reduce the bycatch of unwanted species through behavioural stimulation. Previous studies used LED lights to either highlight escaping routes or increase the contact rate with square-mesh panels. However, phototactic responses (moving towards or away from light sources) to LED lights could also be exploited to separate species during the catching process. We investigated if either positive or negative phototaxis can be used to improve fish vertical separation from Nephrops ( Nephrops norvegicus ) in the aft section of a horizontally separated trawl codend. The aim was to increase the proportion of fish entering the upper compartment. We conducted two different experiments in front of the separation into compartments, inserting green LED lights in the upper and lower netting panel, respectively. Species vertical separation was analysed and compared in two identical trawls towed in parallel, one equipped with lights and one without. We obtained significant changes in vertical separation, but no clear species-specific phototactic response was identified. Neither of the light positions improved fish separation from Nephrops . However, the potential of LED lights as behavioural stimulators is confirmed, and a more mechanistic understanding of light and fish vision may improve the results of future applications.